Ultrafast ultrasonic-assisted joining of bare α-alumina ceramics through reaction wetting by aluminum filler in air. Issue 16 (December 2016) - Ji, Hongjun; Cheng, Xiao; Li, Mingyu
Abstract: Bare α-alumina ceramics were directly bonded together in air through ultrasonic-assisted joining by pure aluminum filler within seconds. It was found that rapid wetting through in-situ reaction of elemental aluminum and oxygen, undercutting of the melted aluminum on ceramic surfaces, and large scale growth of fresh nano-sized alumina particles probably combined successively during the joining, attributing to the acoustic cavitation, the streaming and the micro-jetting by ultrasound effects. Ceramic-composed joints were successfully obtained with fracture strength of 101.5 MPa within 90 s at as low as 973 K.